1957
DOI: 10.1172/jci103550
|View full text |Cite
|
Sign up to set email alerts
|

General Hemodynamics and Splanchnic Circulation in Patients with Coarctation of the Aorta1

Abstract: Controversy concerning the general hemodynamic pattern associated with coarctation of the aorta revolves primarily about the genesis of the systemic arterial hypertension, and the nature and distribution of the peripheral arterial resistance. It is generally agreed (2, 3) that both systolic and diastolic blood pressure levels are elevated above the site of constriction and that the systolic elevation is relatively greater than the diastolic, so that a wide pulse pressure is seen. It is further agreed (2, 3) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1959
1959
1994
1994

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…32 Structural Effects of Hypotensive Treatment Smooth and cardiac muscle, like skeletal muscle, will respond to an increased load by an increase in the quantity of muscle. 1 Thus, in essential hypertension, as for perhaps less complex forms of hypertension (e.g., aortic coarctation 33 ), an increased quantity of cardiac muscle and smooth muscle may be expected in the structures exposed to the increased pressure. The cardiac hypertrophy and increased arterial wall to lumen ratio of hypertensive persons are therefore likely to be at least partly due to the increased blood pressure, 8 and hypotensive treatment may therefore be expected to cause regression of these abnormalities.…”
Section: Hypotensive Action Of Hydralazinementioning
confidence: 99%
“…32 Structural Effects of Hypotensive Treatment Smooth and cardiac muscle, like skeletal muscle, will respond to an increased load by an increase in the quantity of muscle. 1 Thus, in essential hypertension, as for perhaps less complex forms of hypertension (e.g., aortic coarctation 33 ), an increased quantity of cardiac muscle and smooth muscle may be expected in the structures exposed to the increased pressure. The cardiac hypertrophy and increased arterial wall to lumen ratio of hypertensive persons are therefore likely to be at least partly due to the increased blood pressure, 8 and hypotensive treatment may therefore be expected to cause regression of these abnormalities.…”
Section: Hypotensive Action Of Hydralazinementioning
confidence: 99%
“…It is presumed that this elevation of pressure results from failure of the pressure inside the vessels to stretch the pressoreceptors, thereby nullifying the normal inhibitor effect on the vasomotor center by the pressoreceptors. Culbertson et al (250) have observed that the hemodynamic pattern of human hypertension in coarctation of the aorta is quite different from that observed in essential hypertension or renal hyper tension. For instance, evidence for renal ischemia was found in only one of eight such patients, except in those in congestive heart failure, and there was no evidence of generalized vasoconstrictor influence throughout the body.…”
Section: Abnormalities Of the Peripheral Circulationmentioning
confidence: 96%
“…In both patients, moreover, the coarctation was complicated by valvular heart disease. Culbertson et al (1957) while studying the hepatic and renal circulations in this condition, reported a high or normal resting cardiac output in eight patients and an abnormally low cardiac output in two others with left ventricular failure.…”
mentioning
confidence: 98%